2022
DOI: 10.3389/fimmu.2022.847345
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death Tunes Tumor Immunity

Abstract: The demise of cells in various ways enables the body to clear unwanted cells. Studies over the years revealed distinctive molecular mechanisms and functional consequences of several key cell death pathways. Currently, the most intensively investigated programmed cell death (PCD) includes apoptosis, necroptosis, pyroptosis, ferroptosis, PANoptosis, and autophagy, which has been discovered to play crucial roles in modulating the immunosuppressive tumor microenvironment (TME) and determining clinical outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 233 publications
(194 reference statements)
0
120
0
Order By: Relevance
“…Accumulating evidence has revealed that necroptosis genes play an important role in cancer initiation and progression ( 9 , 10 ). Necroptosis genes are also involved in tumorigenesis, distant metastasis and immunosuppression ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has revealed that necroptosis genes play an important role in cancer initiation and progression ( 9 , 10 ). Necroptosis genes are also involved in tumorigenesis, distant metastasis and immunosuppression ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the data sample size and other factors. However, NRGs have been reported to influence the tumor microenvironment 47 , 48 . In addition, tumor microenvironment and immune cells have influenced prognosis in different tumors 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol exposure can also overexpress thioredoxin-interacting protein (TXNIP) by stimulating liver cells, which, in turn, activates NLRP3 inflammasomes and caspase-1-mediated cell typical pyroptosis [ 33 ]. Autophagy, a mechanism of cell survival under conditions of nutritional stress, has also been implicated in the progression of ALD [ 34 ]. It is noteworthy that autophagy regulation is different between acute and chronic ethanol exposure [ 35 ].…”
Section: Pathogenesis Of Aldmentioning
confidence: 99%